The Potential Role of Daucus carota Aqueous and Methanolic Extracts on Inflammation and Gastric Ulcers in Rats - Wehbe, Katia (2009)
Daucus carota (DC) is among commonly used plants in folk medicine in Lebanon and the region. The present investigation was undertaken to examine the effects of the aqueous and extracts of Daucus carota umbels against acute and chronic inflammation, gastric ulcer and antibacterial activity on rats. The effects of DC aqueous extract (DCAE) on glycemia, lipemia, hepatic, renal and pancreatic function were also examined. Results on acute inflammation showed that the aqueous and methanolic extracts (DCME) produced maximum anti-inflammatory activity at doses of 400 and 140 mg/kg body weight with 90.9 and 58.6 % inhibition, respectively. In chronic inflammation, the same doses showed maximum anti-inflammatory activity with 58 and 44.1 % inhibition, respectively. DCME showed significant protection against ethanol induced gastric ulcer with a curative ratio of 46.8 and 68.7%, respectively, at a dose of 250 mg/kg body weight. None of the extracts showed significant antibacterial activity. DCAE intake (250 mg/kg body weight) for one month period did not show adverse effects on lipemia, glycemia, hepatic and liver function except for a slight decrease in HDL cholesterol (p<0.05). In conclusion, both DCAE and DCME exhibited promising anti-inflammatory and anti-ulcerogenic potentials while showing no negative influence on liver, kidney and pancreas function.